Association between subclinical thyroid dysfunction and change in bone mineral density in prospective cohorts. (16th October 2017) - Segna, D.; Bauer, D. C.; Feller, M.; Schneider, C.; Fink, H. A.; Aubert, C. E.; Collet, T.‐H.; da Costa, B. R.; Fischer, K.; Peeters, R. P.; Cappola, A. R.; Blum, M. R.; et al.
Abstract: Background: Subclinical hyperthyroidism (SHyper) has been associated with increased risk of hip and other fractures, but the linking mechanisms remain unclear. Objective: To investigate the association between subclinical thyroid dysfunction and bone loss. Methods: Individual participant data analysis was performed after a systematic literature search in MEDLINE/EMBASE (1946–2016). Two reviewers independently screened and selected prospective cohorts providing baseline thyroid status and serial bone mineral density (BMD) measurements. We classified thyroid status as euthyroidism (thyroid‐stimulating hormone [TSH] 0.45–4.49 mIU/L), SHyper (TSH < 0.45 mIU/L) and subclinical hypothyroidism (SHypo, TSH ≥ 4.50–19.99 mIU/L) both with normal free thyroxine levels. Our primary outcome was annualized percentage BMD change (%ΔBMD) from serial dual X‐ray absorptiometry scans of the femoral neck, total hip and lumbar spine, obtained from multivariable regression in a random‐effects two‐step approach. Results: Amongst 5458 individuals (median age 72 years, 49.1% women) from six prospective cohorts, 451 (8.3%) had SHypo and 284 (5.2%) had SHyper. During 36 569 person‐years of follow‐up, those with SHyper had a greater annual bone loss at the femoral neck versus euthyroidism: %ΔBMD = −0.18 (95% CI: −0.34, −0.02; I 2 = 0%), with a nonstatistically significant pattern at the total hip: %ΔBMD = −0.14 (95% CI: −0.38, 0.10; I 2 = 53%), but not at the lumbar spine: %ΔBMD = 0.03 (95% CI: −0.30, 0.36; I 2 = 25%); especially participants with TSH < 0.10 mIU/L showed an increased bone loss in the femoral neck (%Δ BMD = −0.59; [95% CI: −0.99, −0.19]) and total hip region (%ΔBMD = −0.46 [95% CI: −1.05, −0.13]). In contrast, SHypo was not associated with bone loss at any site. Conclusion: Amongst adults, SHyper was associated with increased femoral neck bone loss, potentially contributing to the increased fracture risk.